KAMPANYE POLITIK BERBASIS KEARIFAN LOKAL: ANALISIS KOMUNIKASI POLITIK MELALUI WAYANG GOLEK PADA PILKADA BANDUNG 2024 - Aura Ramadhanisa; Riyan Jaelani (Fakultas Politik Pemerintahan, 2026)
This study analyses the political communication of the candidate pair for Regent and Deputy Regent of Bandung, Dadang Supriatna–Ali Syakieb, through Wayang Golek performances in the 2024 Bandung Regency elections, and identifies the supporting and inhibiting factors that influence its effectiveness. The approach used is descriptive qualitative with data collection techniques through in-depth interviews and documentation studies of puppeteers, party leaders, campaign teams, and community leaders. Data analysis used the Miles and Huberman model, while the theoretical framework used was Cangara's Political Campaign Theory (2023), which includes four indicators: communicator determination, target audience determination, campaign message formulation, and media selection. The results of the study show that political communication through Wayang Golek was successfully implemented based on these four indicators. The puppeteer acted as a credible main communicator; the performances were focused on rural areas as a strategic target segment; the campaign messages contained concrete programmes such as incentives for Quran teachers and the Rutilahu programme; and Wayang Golek proved to be an effective medium thanks to the power of its cultural appeal. Supporting factors included strong traditional values, adaptability to the times, the effectiveness of messages through symbolic narratives, emotional closeness to the community, and high public enthusiasm. Meanwhile, inhibiting factors included limited regional access, cost constraints, and weather factors. This study confirms the relevance of traditional arts and culture as an effective instrument of political communication in the era of digitalisation, particularly in reaching communities with strong local cultural ties.